Integrated Framework for Renewable Energy Transition in Continental Heavy Manufacturing Supply Chains: A Critical Review - Ahya Hidayat (JADI (Jurnal Teknik Industri), 2026)
The accelerating transition toward industrial decarbonization presents a profound dilemma for heavy manufacturing supply chains: balancing carbon mitigation targets with operational resilience against systemic disruptions. This study conducts a systematic literature review synthesizing 20 core studies (n = 20) using the PRISMA 2020 framework to resolve the theoretical tension between decarbonization and supply chain viability across steel, chemical, automotive, and cement sectors. Synthesized evidence is structured around three foundational pillars: structural disruption vectors, renewable energy enablers, and structural resilience capabilities. Findings reveal that traditional risk management strategies, such as safety stock buffering and localized dual-sourcing, are insufficient when facing systemic geopolitical frictions, critical material bottlenecks, and carbon pricing pressures. Instead, an integrated conceptual framework demonstrates that clean energy integration, including green hydrogen blending, hybrid microgrids, and long-term Corporate Power Purchase Agreements, functions as a direct catalyst for reinforcing absorptive capacity, adaptive flexibility, and restorative continuity. This paper contributes an operational architecture that redefines decarbonization from a compliance burden into a strategic driver of long-term continental supply chain resilience.